Development of Simple Kinetic Model on Biogas Production from Co-Digestion of Vinasse Waste and Tofu Residue at Variation of C/N Ratio - Syaichurrozi, Iqbal; Rusdi, Rusdi (World Chemical Engineering Journal, 2020)
The Generated Biogas Rate (GBRT) model and the Predicted Maximum Biogas Potential and Yield (PMBPY) model were developed in this work for better understanding of the anaerobic co-digestion of vinasse waste and tofu residue at variation of total carbon/total nitrogen (C/N) ratio which was 3.71, 5.26, 7.30, 32.54, 97.34. Rate constant (k (/day)) and biogas production rate (ū (mL/day)) estimated using GBRT model was 0.071, 0.140, 0.153, 0.150, 0.125 /day and 20.206, 101.393, 111.832, 95.967, 58.616 mL/day respectively for all variables (R2 of 0.925 – 0.976). The maximum biogas potential (Pm) obtained using PMBPY model for all variables was 335.8317, 737.0868, 760.4523, 608.3871, 523.3872 mL respectively (R2 = 0.914 – 0.972). The fitting error between measured biogas and predicted biogas through the developed model was 0.20 – 7.03 %. The developed kinetic model can predict biogas potential with prediction efficiency (%) over modified Gompertz model of 91.71 – 98.57%.